PENERAPAN MODEL PEMBELAJARAN INQUIRY TRAINING UNTUK MENINGKATKAN HASIL BELAJAR FISIKA PADA SISWA KELAS X SMA N 4 PEKANBARU - Dwi Athifah Ramadhani; Mitri Irianti; M. Nor ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this study was to determine the increase in Physics Learning Outcomes class X SMA N 4 Pekanbaru using model Inquiry Training. The research was conducted of the month April 2017 to July 2017. The form of this study was Quasi Experimental Design with design Intact Group comparasion. The sample of research in class X1 and X2 with the number of students 38 and 37 students in SMA N 4 Pekanbaru. Where in class X2 as experiment class and class X1 as control class. The research instrument used is test result of cognitive learning. Data collection techniques are tests of cognitive learning outcomes. Data analysis techniques used are descriptive and inferential analysis.The results showed that the average score of the absorption of students with the application of training inquiry is 71.51% with the higher category, while the average absorption class with the application of conventional learning 63.71% with a lower category. Thus concluded that the application of learning models Inquiry Training can improve student learning outcomes in learning Physics in harmonious vibration material in class X SMA N 4 Pekanbaru.Keywords: Inquiry Training model, learning outcomes.